People management: case study of the organizational climate in a public institution (Research, Society and Development, 2020)
This paper analyzed the influence of factors that affect the organizational climate within a public organization. The general objective was to diagnose the perception and satisfaction of the technical and administrative employees of the Paraíba State Department of Education in relation to the work environment, suggesting actions that help the organization to overcome its weaknesses, in line with the results obtained. Of the universe of 197 civil servants, 120 participated in the survey, representing 61% of the administrative staff of the investigated body. The methodology adopted was bibliographic and field research, using a data collection questionnaire based on the Burke-Litwin model, integrated by twelve dimensions that influence the performance of the organization, relating them to its management model, culture , structure and internal climate. The analysis and interpretation of the data took place using a quantitative approach. With regard to the literature review, topics related to organizational behavior, people management, internal relationships, leadership, quality of life at work, motivation and organizational climate were addressed. From the results obtained, it was concluded that the respondents are moderately satisfied with their work environment, standing out as elements for an immediate corrective action the demotivation of the employees, especially in relation to salary, benefits and recognition, as well as the dissatisfaction with the relationship maintained with the top management of the organization.